Behavioral relevance of species-specific vasotocin anatomy in gregarious finches - Kelly, Aubrey M.; Goodson, James L. (Frontiers in Neuroscience, 2013)
Despite substantial species differences in the vasotocin/vasopressin (VT/VP) circuitry of the medial bed nucleus of the stria terminalis (BSTm) and lateral septum (LS; a primary projection target of BSTm VT/VP cells), functional consequences of this variation are poorly known. Previous experiments in the highly gregarious zebra finch (Estrildidae: Taeniopygia guttata) demonstrate that BSTm VT neurons promote gregariousness in a male-specific manner and reduce anxiety in both sexes. However, in contrast to the zebra finch, the less gregarious Angolan blue waxbill (Estrildidae: Uraeginthus angolensis) exhibits fewer VT-immunoreactive cells in the BSTm as well as differences in receptor distribution across the LS subnuclei, suggesting that knockdown of VT production in the BSTm would produce behavioral effects in Angolan blue waxbills that are distinct from zebra finches. Thus, we here quantified social contact, gregariousness (i.e. preference for the larger of two groups), and anxiety-like behavior following bilateral antisense knockdown of VT production in the BSTm of male and female Angolan blue waxbills. We find that BSTm VT neurons promote social contact, but not gregariousness (as in male zebra finches), and that antisense effects on social contact are significantly stronger in male waxbills than in females. Knockdown of BSTm VT production has no effect on anxiety-like behavior. These data provide novel evidence that species differences in the VT/VP circuitry arising in the BSTm are accompanied by species-specific effects on affiliation behaviors.